Tinjauan Yuridis Penerapan Notifikasi Akuisisi Sebagai Upaya Pencegahan Persaingan Usaha Tidak Sehat - Florianus Yudhi Priyo Amboro; Hermanto Hermanto (Fakultas Hukum, Universitas Internasional Batam, 2018)
The main goal of the notification of acquisition is as prevention effort of unfair business competition practice. This research was conducted to analyze implementation of notification on acquisition as an effort to prevention, analyzes role of Komisi Pengawas Persaingan Usaha to assess and analyzes notification assessment standards was done with notification on acquisition. Case approach that used for this research is acquisition Axis by XL Axiata and acquisition Lafarge by Holcim. Research methodology used is juridical normative. Research normative juridical use of law primary, secondary and tertiary and using data primary. To obtain the data used method of literature study and interview. But the approach used in this research is the approach cases and statute approach. Based on the results of research that has been done so in reality the implementation of the notification is an effort to prevent monopolistic practices and unfair business competition. But the implementation of the acquisition notification is not currently reflecting the efforts to prevent, this can be seen from opinion of Komisi Pengawas Persaingan Usaha related acquisition Axis by XL and acquisitions Lafarge by Holcim. A technical an appraisal that stipulated in the Peraturan Komisi Pengawas Persaingan Usaha Nomor 3 Tahun 2012 has not given the head of house of the efforts to prevent.